2016 IEEE Symposium Series on Computational Intelligence (SSCI) 2016
DOI: 10.1109/ssci.2016.7850280
|View full text |Cite
|
Sign up to set email alerts
|

A Facility Layout Planner tool based on Genetic Algorithms

Abstract: Abstract-Nowadays, in order to maintain their competitiveness, manufacturing companies must adapt their production methods quickly, with minimum expenditure, to frequent variations on demand. With the shortage of the product life time, flexibility, efficiency and reusability of industrial processes are important factors, which may determine the survival of the company. The ReBORN project is working around these ideas, namely studying how can an old production equipment be reused into new contexts. The ReBORN W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…AI-based smart systems have been demanded in complex environments where new approaches are needed to achieve optimal performance. For these purposes, it has been observed that different evolutionary computation techniques [108] (genetic algorithms [109], swarm intelligence [110], discrete differential evolution algorithms [111], neuroevolutionary learning techniques [112]) obtain good results and improve the multi-criteria optimization problems that take place in such extreme contexts [113], by providing a holistic approach, taking into consideration not only parameters but also topologies and rules.…”
Section: Deep Learningmentioning
confidence: 99%
“…AI-based smart systems have been demanded in complex environments where new approaches are needed to achieve optimal performance. For these purposes, it has been observed that different evolutionary computation techniques [108] (genetic algorithms [109], swarm intelligence [110], discrete differential evolution algorithms [111], neuroevolutionary learning techniques [112]) obtain good results and improve the multi-criteria optimization problems that take place in such extreme contexts [113], by providing a holistic approach, taking into consideration not only parameters but also topologies and rules.…”
Section: Deep Learningmentioning
confidence: 99%
“…Dong et al [15] applied the simulation engine to establish the three-dimensional model of the equipment and the layout of the workshop to realize the combination of virtual and reality. Pinto et al [16] studied the layout of the workshop with ReBORN Workbench and a genetic algorithm. Liao et al [17] established the three-dimensional model on Visual Components and designed the layout of the workshop with the systematic layout planning (SLP) method.…”
Section: Related Studiesmentioning
confidence: 99%
“…In this paper, the genetic algorithm is used to solve the model. The genetic algorithm can be independent of the specific field of the problem and has strong robustness to this type of the problem [45][46][47][48][49][50]. Therefore, the genetic algorithm can solve the layout problem of the cabin equipment.…”
Section: Genetic Algorithm Designmentioning
confidence: 99%